Face Recognition Algorithm Comparison based on Backpropagation Neural Network - Li, Pan; Zhang, Qian (Journal of physics. Conference series, 2021)
Face recognition is a hot research direction in the field of computer in recent years. Due to the constant update and progress of computer hardware technology and software algorithm, face recognition technology is becoming more and more perfect, and face recognition technology starts to appear in different fields. Because of the high security of face recognition, we can design a face recognition access control system based on backpropagation neural network. This paper mainly compare three different face recognition algorithms based on matlab and test the accuracy of these algorithms.